The link between systemic inflammation and mental disorders: a study on CLR, depression, and anxiety in a US cohort - Su, Yue; Ge, Yuhan; Yang, Hui; Zhai, Guojie; Cheng, Xiaolan (Frontiers in Psychiatry, 2025)
BackgroundDepression and anxiety are significant global health concerns, with systemic inflammation playing a critical role in their pathophysiology. Recent studies have highlighted the C-reactive protein to lymphocyte ratio (CLR) as a potential biomarker of inflammation that may be associated with these mental health conditions. However, the relationship between CLR and depression and anxiety, especially within a diverse population, remains underexplored.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) (2015–2023) to examine the association between CLR and the prevalence of depression and anxiety. A total of 22,308 participants were included for depression analysis, and 16,138 participants were included for anxiety analysis. Depression was assessed using the PHQ-9, and anxiety was assessed through self-reported anxiety symptoms and medication use. CLR was calculated as the ratio of C-reactive protein to lymphocyte count, and logistic regression models were applied to analyze associations, adjusting for demographic and health-related variables.ResultsHigher CLR levels were significantly associated with increased odds of depression (OR: 1.49; 95% CI: 1.25–1.78) and anxiety (OR: 1.13; 95% CI: 1.02–1.26) after full adjustment for confounders. Non-linear relationships were observed, with specific inflection points for both depression (CLR = 0.96) and anxiety (CLR = 0.88), beyond which the risk of mental health disorders increased sharply. Subgroup analyses revealed that younger individuals and those without hypertension showed stronger associations between CLR and depression.ConclusionElevated CLR is associated with an increased risk of depression and anxiety, suggesting the potential role of systemic inflammation in influencing mental health outcomes. CLR may serve as a useful biomarker for identifying populations at higher risk, underscoring the need for further research into early intervention strategies and targeted approaches to address systemic inflammation in mental health care.